State, social control and symbolic appropriations - Castro-Blanco, Elías (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Elías Castro PhD, who fled the infected metropolis to take refuge in the warmth of El Socorro, presents a Foucauldian vision of social control, where there are various forms of repression or discipline for those who act outside of positive norms. The symbolic appropriations are important representations that the individual performs to act according to the standard, on pain of suffer the sanction of the case.